Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21608/eajbsf.2018.22726
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artemisia judaica Extract and Certain Insecticides against Cotton Leafworm, Spodoptera littoralis (Lepidoptera: Noctuidae)

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Also, Louni et al [19] the mortalities of Ephestia kuehniella were 84% on the 1 st day when treated with M. longifolia oil at 40000 ppm. The highest mortality up to 16 days of the S. littoralis exposed to A. judaica mixed with Chromafenozide was 70 and 77% at 72 and 96 hrs, respectively [17].…”
Section: Fig 1 Larval Mortality Of a Ipsilonmentioning
confidence: 92%
See 1 more Smart Citation
“…Also, Louni et al [19] the mortalities of Ephestia kuehniella were 84% on the 1 st day when treated with M. longifolia oil at 40000 ppm. The highest mortality up to 16 days of the S. littoralis exposed to A. judaica mixed with Chromafenozide was 70 and 77% at 72 and 96 hrs, respectively [17].…”
Section: Fig 1 Larval Mortality Of a Ipsilonmentioning
confidence: 92%
“…Elbadawy et al [16] indicated that jojoba oil was most effective against the 4 th instar larvae of A. ipsilon, causing 60% mortality. Additionally, botanical extracts as antioxidants have been applied to many other lepidopterous insects such as Spodoptera littoralis [17], Spodoptera frugiperda [18].…”
Section: Introductionmentioning
confidence: 99%